Rights of Nature and Constitutional Jurisprudence in Ecuador - Solano Paucay, Vicente (2024)
This article examines the development of Nature rights in Ecuador through constitutional jurisprudence. The recognition of these rights challenges the anthropocentric paradigm and aims to protect life from a counter-hegemonic perspective. However, it is essential to carefully evaluate these constitutional innovations and their implications in the Ecuadorian legal system.Ecuador became the frst country to constitutionally grant rights to nature in 2008, establishing a comprehensive legal framework for its protection. This study analyzes the jurisprudence of the Ecuadorian Constitutional Court from 2008 to 2022 to understand the implementation of these rights. The research focuses on jurisprudence due to the vagueness of legislation and the lack of infraconstitutional development. Among the key fndings are the specifc and generic nature of nature rights, the open catalog of rights, and the content of these rights. The study also explores principles such as pro natura favorability and precaution, emphasizing the importance of applying various constitutional guarantees for their protection. Finally, the Ecuadorian Constitutional Court, through its interpretive activity in its jurisprudence, established the recognition of animals as subjects of rights, contributing to their protection and promoting an ecological approach, advancing toward a biocentric paradigm that safeguards Nature.